A II. Orbán-kormány gazdaságpolitikájának néhány jellemzője 2010 nyara és 2012 tavasza között - Gősi, János (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
The economic policy of the II. Orbán-governmcnt in the net of politics. Taxes crisis: banking, commerce, etc. The flat-rate personal income tax Compulsory membership of private pension funds nationalization of assets The fixed rate of repayment of foreign currency loans recorded a large loss for the banks. The aim of Fidesz-KDNP: economic policy without restriction for the 2014 election to win. Independence against the requirements of the EU and the IMF. II. Orbán government's economic policy for international confidence decreased.